Mechanical characterization of a prototype a-C:Cr, Si and its tribological behavior at high temperature. (August 2016) - Staia, M.H.; Dubar, L.; Dubar, M.; Puchi-Cabrera, E.S.; Iost, A.; de Baets, P.; Dubois, A.
Abstract: The results of the mechanical and tribological characterization of a prototype a-C:Cr, Si sputtered coating are presented. The hardness and the elastic modulus of the coated system have been determined by means of nanoindentation taking into account the actual architecture of the bi-layer coating. Both mechanical properties were recorded continuously versus the indentation depth, h, up to approximately 2000 nm, at a constant indentation rate and maximum applied loads of 700 mN. The results were analyzed by means of the Oliver and Pharr method and modeled on the basis of novel approach proposed recently by some of the authors. Wear tests were conducted at 25 °C, 400 °C and 450 °C against alumina, employing a contact pressure of 540 MPa. Characterization of the worn surfaces by SEM and elemental X-ray mapping has also been carried out. A wear rate as low as 1.2×10 −18 m 3 /N m was determined for the coating tested at 25 °C, which is approximately one order of magnitude and three times less than those found from the tests performed at 400 °C and 450 °C, respectively. It has been determined that the a-C:Cr, Si coating exhibits a very good wear resistance even at temperatures up to 450 °C, as consequence of the Si and Cr oxides formed due to the oxidation process. Also, it has found that at this temperature, a continuous oxide film is formed, which reduces the wear rate of the coated system in comparison to that determined at 400 °C. However, the volume increase due to the oxidation process at 450 °C and the elimination of CO2, Ar and H2 O vapors, induces a severe surface cracking of the coating. Highlights: High temperature sliding wear of a prototype a-C:CrSi coating has been investigated. Mechanical properties of the coating have been determined by nanoindentation. Elemental X-Ray mapping indicated the existence of Si and Cr oxides at 450 °C. The coated system showed satisfactory wear behavior at temperature as high as 450 °C.